Literature Review: The Effectiveness of Madrasah Principal Supervision in Improving Teacher Discipline - Vera Monica; Subandi; M. Kharis Fadillah (Journal of Educational Management Research, 2026)
This study aims to examine the effectiveness of madrasah principal supervision in improving teacher discipline based on findings from previous studies. A literature review method with a descriptive qualitative approach was employed. The data consisted of 16 scholarly articles related to madrasah principal supervision, educational supervision, leadership, teacher discipline, and teacher performance. Data were analyzed using thematic synthesis by categorizing findings into four themes: supervision practices, the impact of supervision on teacher discipline, supporting factors, and inhibiting factors. The results indicate that effective supervision is implemented through academic supervision, attendance monitoring, performance evaluation, coaching, communication, role modeling, and the application of reward and punishment systems. Supervision that is systematic, consistent, communicative, and supported by clear follow-up actions contributes significantly to improving teacher discipline. Supporting factors include communicative leadership, clear disciplinary regulations, continuous coaching, motivation, adequate facilities, and exemplary behavior from the principal. In contrast, limited time, insufficient facilities, weak follow-up, low teacher awareness, and resistance to evaluation hinder supervision effectiveness. The findings imply that madrasah principal supervision should be conducted in a collaborative, continuous, and supportive manner to foster a disciplined work culture and strengthen teacher professionalism.